The position and authority of the Aceh Shari'a court on the Indonesian justice system - Sufiarina, Sufiarina (UI Scholars Hub, 2015)
Article 27 paragraph (1) of Law No. 48 Year 2009 regarding Judicial Power states that special courts can only be formed in one of the court systems under the Supreme Court, which include general courts, religious courts, military courts and state administration courts. However, article 3A paragraph (2) of Law No. 50 Year 2009 concerning the Second Amendment to the Law on Religious Court places Shariah Court as a special court within the system of religious courts and as a special court within the system of general courts. Such positioning is inconsistent with Article 27 paragraph (1) of the Law on Judicial Power which raises a legal issue and therefore requires juridical solution. The inconsistency is subject to juridical normative study within the scope of a research concerning the level of horizontal synchronization, using descriptive analysis. The method applied for data collection in this research is through literature study supported by field data. The data obtained is analyzed by using juridical qualitative method. This study concludes that, in fact, the Shariah Court is neither a special court, nor does it stand in two systems of courts. Both in terms of general administration as well as case management, the Shariah Court is a Religious Court for the territory of the Province of Nanggroe Aceh Darussalam, the competence of which has been expanded in the context of the implementation of special autonomy, particularly in the field of the implementation of Islamic shari’a.